2002
DOI: 10.1209/epl/i2002-00418-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced counterion localization induced by surface charge modulation

Abstract: Using both small-amplitude and singular-perturbation theories we predict theoretically that the presence of surface charge modulations gives rise to an enhancement of the counterion density near the surface above and beyond that of a uniform, charged surface. We confirm these predictions with Monte Carlo simulations. Our study focuses on the weak- to moderate-coupling regime which is complementary to a similar investigation performed by Moreira and Netz (Europhys. Lett., 57 (2002) 911) in the strong-coupling c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
52
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 21 publications
13
52
0
Order By: Relevance
“…This in turn implies that φ(z; N b > 0) > φ(z; 0) for any z > 0. Thus, the two state model predicts that charge discretization of a planar macromolecule leads to enhanced counterion localization, in agreement with the results of [5,6].…”
supporting
confidence: 85%
See 2 more Smart Citations
“…This in turn implies that φ(z; N b > 0) > φ(z; 0) for any z > 0. Thus, the two state model predicts that charge discretization of a planar macromolecule leads to enhanced counterion localization, in agreement with the results of [5,6].…”
supporting
confidence: 85%
“…For small charge modulation, it is appropriate to use a perturbative expansion of the Poisson-Boltzmann (PB) equation to describe the meanfield behavior of the counterion distribution. It has already been shown that such an expansion leads to enhanced counterion localization for planes [6], and it is straightforward to show that the same conclusion holds for surfaces of arbitrary geometry [13]. For a discrete surface charge distribution, however, pair association between discrete macromolecular charges and the discrete counterions [14,15] can become important; that is, a large number of counterions can become localized near the macromolecular surface.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Collapse of counterions and surface ions is prevented by a truncated Lennard-Jones term acting between all particles. The model we consider includes the combined effects of discrete surface charges, surface corrugations, and counterion excluded volume [123], which are all neglected in the classical mean-field approaches but have been considered quite recently [54,124,125,91,126,127,128,129,130,131,132,133]. We employ Browniandynamics simulations where the velocity of all particles follows from the position Langevin equation.…”
Section: Charged Structured Surfacesmentioning
confidence: 99%
“…The presence of excess ionic polarizabilities was proposed to lead to corrections to the usual van-der-Waals interaction energy, which could be one of the factors determining ion-specific interactions [293,294,295,296]. But it was also shown that even with pure Coulomb interactions, one obtains strong deviations from the standard mean-field approaches if one takes into account that the charge distribution on all charged surfaces is laterally modulated [54,124,125,127,128]. Specifically, the counterion density right at a charged surface (which for a homogeneously charged surface and in the absence of additional interactions is exactly given by Eq.…”
Section: Ion-specific Effectsmentioning
confidence: 99%